Post-Tridentine Mass Attendance as Devotion to the Suffering Christ - Achen, Henrik von (Religions, 2022)
Continuing the long tradition of the allegorical interpretation of the Mass, the seventeenth- and eighteenth century ideal of proper mass attendance was devotion to the suffering Christ, inextricably linked to each step of the liturgy. In this article, post-Tridentine mass books, booklets, or chapters on the mass in devotional books for lay people, are investigated to understand the praxis pietatis in which they were embedded. These texts served devotional and educational purposes outside mass as well, but primarily they reveal a concerted effort to promote active participation of lay people at mass. In the post-Tridentine era, the mass books for lay people became a kind of Passional, serving active participation of the faithful at mass as a devotional practice configured to the actions of the priest as mass progressed. Joining Ordo and Passion, the mass books combined two dimensions of the one sacrifice with the main objective being to support a heartfelt, attentive focus on both. Based on the mass books and other devotional texts investigated, no sharp distinction can be made between attending the formal liturgy and engaging in a devotional practice as the Passion narrative unfolded in, and by, the actions of the priest.